The co-occurrence of terracotta wheelmade figures and handmade figurines in mainland Greece, Euboea, the Dodecanese, the Cyclades and the Northern Aegean islands, 1200-700 BC - Thurston, C; Caroline A Thurston (2015)
This thesis addresses the lacuna in the study of Greek terracotta figures and figurines corresponding to the transitional period between the Late Bronze and Early Iron Ages (1200-700BC). It provides a comprehensive synthesis of all available data, with particular reference to material from recently excavated sites in mainland Greece and its islands (Euboea, the Northern Aegean islands, the Dodecanese and the Cyclades). The study is framed according to the relationship between terracotta figures (those made on the potter's wheel) and figurines (those made by hand). The observation that the technological distinction between these two types is reflected in their different and separate functions has been sustained in scholarship for the past three decades, but only for the Mycenaean period. Handmade figurines and wheelmade figures occurred in different and restricted contexts in the Mycenaean world: the former in settlements, cemeteries and religious locations, and the latter exclusively in religious contexts. It is therefore inferred that they had different socially embedded values or 'meanings'. However, the extent to which such a distinction applies to figures and figurines in the Early Iron Age has hitherto not been explored. Initial evidence indicates that by the 8th century, handmade figurines and wheelmade figures were deposited together at selected sites, suggesting that their inherent socially embedded meanings were the same, and that they represented "different levels of [financial] investment in what is essentially the same category of votive". This thesis therefore determines the levels of co-occurrence of wheelmade figures and figurines, thus identifying how distribution relates to usage. Changes are observed over time and space and between different types of functional contexts, and the meanings of these patterns are investigated. The results of this study provide a chronological and geographical overview of the distribution of figures and figurines, and also indicate that figures and figurines had consistently multivariate relevance in multiple types of contexts. The functional dichotomy of figures and figurines observed for the Mycenaean period cannot be sustained beyond 1200 BC. Moreover, study of the contexts from which the material originates indicates that the significance of secondary deposits of religious nature has been consistently overlooked, and that figures and figurines were used in an active and meaningful sense even during the act of their discard. This type of activity is a distinctive one that can be characterised and defined functionally, geographically, temporally and quantitatively. The socially embedded meaning of figures and figurines was fluid and related to an action being performed; their meaning was not linked exclusively to an aspect of the object itself, and was therefore not static.